If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 2y = 2y + -6 + y Combine like terms: -4y + 2y = -2y -2y = 2y + -6 + y Reorder the terms: -2y = -6 + 2y + y Combine like terms: 2y + y = 3y -2y = -6 + 3y Solving -2y = -6 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -2y + -3y = -6 + 3y + -3y Combine like terms: -2y + -3y = -5y -5y = -6 + 3y + -3y Combine like terms: 3y + -3y = 0 -5y = -6 + 0 -5y = -6 Divide each side by '-5'. y = 1.2 Simplifying y = 1.2
| 49v^4-16t^2=0 | | y=-6(1) | | y=-6(0) | | y=-6(-1) | | y=-2(-6)-6 | | y=-2(-9)-6 | | 6(2x-8)=24x | | f(a+2)=a+2+3 | | f(0)=(0)+3 | | 12(7.5-1y)+6y=72 | | 4+(-3)*2= | | 4x+4x=30 | | 26+31=22x+59 | | 6(6-6y)+15y=90 | | f(5)=(5)+3 | | f(-8)=-8+3 | | f(0)=0+3 | | f(2a)=2a+3 | | 12x+6y-6y=72-6y | | (x+8)(x+2)=55 | | 5w-10=6w+9 | | 2a(5+7)= | | r^2+2r+3=0 | | -8x^2+x-16=10x^2-10 | | -5x^2+11x-6=0 | | .089=.0269+x | | -4x^2-5x=-6 | | y=-2x^3+2 | | -x=9x^2-10 | | 10x^2-7x+12=0 | | 12x^2-4x-1=0 | | 15=1(1+g) |